Heart rate and blood pressure monitoring in heart failure - Ponikowski, Piotr (Eur Heart J Suppl, 2019)
It has been long known that incessant tachycardia and severe hypertension can cause heart failure (HF). In recent years, it has also been recognized that more modest elevations in either heart rate (HR) or blood pressure (BP), if sustained, can be a risk factor both for the development of HF and for mortality in patients with established HF. Heart rate and BP are thus both modifiable risk factors in the setting of HF. What is less clear is the question whether routine systematic monitoring of these simple physiological parameters to a target value can offer clinical benefits. Measuring these parameters clinically during patient review is recommended in HF management in most HF guidelines, both in the acute and chronic phases of the disease. More sophisticated systems now allow long-term automatic or remote monitoring of HR and BP and whether this more detailed patient information can improve clinical outcomes will require prospective RCTs to evaluate. In addition, analysis of patterns of both HR and BP variability can give insights into autonomic function, which is also frequently abnormal in HF. This window into autonomic dysfunction in our HF patients can also provide further independent prognostic information and may in itself be target for future interventional therapies. This article, developed during a consensus meeting of the Heart Failure Association of the ESC concerning the role of physiological monitoring in the complex multi-morbid HF patient, highlights the importance of repeated assessment of HR and BP in HF, and reviews gaps in our knowledge and potential future directions.